The analysis of patient preferences for oral and dental care: Factor analysis model - Onur Simsek, Hasan; Yavuzaslan, Kiymet (Annals of Medical Research, 2021)
Aim: This study is the in terms of patient preferences for oral and dental care, as it includes determining the factors that affect the preferences of patients in the treatment of oral and dental care and the analysis of other factors such as how the demographic characteristics are effective in these factors. Materials and Methods: In the study, a 14-item questionnaire form consisting of one section was used. The first 13 items consisted of demographic and descriptive questions. Item 14 consisted of 5-point Likert-type 18 questions regarding the investigation of reasons. The questionnaire was applied by the physician who was responsible for the patient’s treatment.Results: Four factors emerged as a result of the factor analysis. When grouped by the content of the questions included in the factors, the first factor was about the characteristics of the hospital staff, the second factor was about the basic functioning of the hospital, the third factor was about the accessibility of the service provided by the hospital, while the cost factor that can be expressed as the monetary value of the service provided by the hospital consisted of a single question.Conclusion: It was concluded that the quality of treatment service, the approaches of physicians and assistant staff, hospital conditions and access to service and cost were effective in-patient preferences for oral and dental care services. Keywords: Dentistry; factor analysis; health behavior; patient preferences